Study protocol to establish a prospective cohort for the study of phenotypic clusters, progression pathways, and outcomes of frailty and dependence: The CohorFES - Natàlia Garcia-Giralt; Diana Ovejero; Jose Antonio Carnicero Carreño; Anna Ribes; Pedro Abizanda Soler; Jose Antonio Serra Rexach; Francisco José García García; Montse Rabassa; Leocadio Rodriguez Mañas; Àlex Sanchez Pla; Mariam El Assar de la Fuente; Carmen Maria Osuna Del pozo; et al. (PLoS ONE, 2026)
Frailty has become a major challenge for health systems, but it also presents a window of opportunity to fight disability through preventive strategies focused on the detection and treatment of frailty across all care settings. However, no systematic strategies for screening and early detection are currently available in clinical practice. This project aims to identify clinical and biological phenotypic clusters that drive progression through the different stages of frailty, and to describe the underlying mechanisms of the trajectories leading to disability and potential treatment interventions. In addition, the Frailty Trait Scale 5 (FTS5) will be validated as a practical tool for implementation in both primary care and hospital settings. A prospective, population-based cohort (CohorFES) will be established for frailty phenotyping. A CIBERFES Biobank will also be created to store blood and urine samples from CohorFES participants for future research. Demographic and clinical history data, anthropometric measurements, the PREDIMED questionnaire, peripheral blood biochemical variables, and metabolomics data will be collected at baseline and annually until participants develop frailty. Cluster partition models (k-means and hierarchical clustering) will be used to group individuals with similar deficits and characteristics (frailty phenotypes). Then, by using pre-established criteria (gap and silhouette), the proposed clustering solution (belonging to given clusters) will be evaluated. We will also assess, in a longitudinal manner, the emergence and accumulation of deficits over time, identifying subgroups with more rapid progression. The results will be used to define and compare clusters and progression trajectories. Finally, frailty phenotypes and patient clusters will be correlated with health outcomes such as healthcare utilization (primary and secondary care), hospital admissions, and mortality. Information on clinical and biological phenotypic clusters involved in the progression of frailty may help identify potential therapeutic targets to improve the management of these patients. In summary, from a research perspective, this project aims to improve our understanding of the interindividual variability in clinical trajectories that lead to frailty, dependence, and ultimately, death. Protocol Registration: NCT06965972 (date 05/02/2025)